2020
DOI: 10.13057/biodiv/d211250
|View full text |Cite
|
Sign up to set email alerts
|

Euthynnus affinis viscera-an alternative source for protease and lipase enzymes: Characteristic and potential application as destainer agent

Abstract: Abstract. Mardina V, Harmawan T, Fitriani, Sufriadi E, Febriani, Yusof F. 2020. Euthynnus affinis viscera-an alternative source for protease and lipase enzymes: Characteristic and potential application as destainer agent. Biodiversitas 21: 5858-5864. This study described the characterization of protease and lipase, extracted from the viscera of Euthynnus affinis and their applications as stains removal. Enzyme increased a few folds (3.99 folds for protease and 2.45 folds for lipase) after the submission to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…At the above temperature, enzyme activity still exists, leading to protein decomposition and thus reducing the protein content in the spice powder. Based on [32] , it was observed that the protease enzyme is altered when exposed to temperatures above 75°C. This is due to protein aggregation, in which pseudo-clusters coalesce and form clumps, leading to blood clotting.…”
Section: Protein Contentmentioning
confidence: 99%
“…At the above temperature, enzyme activity still exists, leading to protein decomposition and thus reducing the protein content in the spice powder. Based on [32] , it was observed that the protease enzyme is altered when exposed to temperatures above 75°C. This is due to protein aggregation, in which pseudo-clusters coalesce and form clumps, leading to blood clotting.…”
Section: Protein Contentmentioning
confidence: 99%